Diboron‐Assisted Interfacial Defect Control Strategy for Highly Efficient Planar Perovskite Solar Cells. Issue 49 (8th October 2018) - Tu, Yongguang; Yang, Xiaoyu; Su, Rui; Luo, Deying; Cao, Yang; Zhao, Lichen; Liu, Tanghao; Yang, Wenqiang; Zhang, Yifei; Xu, Zhaojian; Liu, Quanzhen; Wu, Jihuai; et al.
Abstract: Metal halide perovskite films are endowed with the nature of ions and polycrystallinity. Formamidinium iodide (FAI)‐based perovskite films, which include large cations (FA) incorporated into the crystal lattice, are most likely to induce local defects due to the presence of the unreacted FAI species. Here, a diboron‐assisted strategy is demonstrated to control the defects induced by the unreacted FAI both inside the grain boundaries and at the surface regions. The diboron compound (C12 H10 B2 O4 ) can selectively react with unreacted FAI, leading to reduced defect densities. Nonradiative recombination between a perovskite film and a hole‐extraction layer is mitigated considerably after the introduction of the proposed approach and charge‐carrier extraction is improved as well. A champion power conversion efficiency of 21.11% is therefore obtained with a stabilized power output of 20.83% at the maximum power point for planar perovskite solar cells. The optimized device also delivers negligible hysteresis effect under various scanning conditions. This approach paves a new way for mitigating defects and improving device performance. Abstract : A diboron‐assisted strategy for tuning interfacial defects in formamidinium‐iodide‐based perovskite solar cells is demonstrated to decompose the unreacted organic‐halide species at the surface by coating B2 Cat2 on top of the perovskite films, which can suppress the nonradiative recombination loss and boost power conversion efficiency. This approach paves a new way for mitigating defects and improving device performance.